Kontribusi Redaktur Deuteronomist dalam Teologi Mikha 3:1-12 - Maria Evvy Yanti; Seno Lamsir (Immanuel: Jurnal Teologi dan Pendidikan Kristen, 2025)
The actuality of colorful interpretations of Micah 3:1-12 results in different theological views as well. Especially when interpreting the theology of review of religious leaders and the government in the textbook. There's an opinion that Micah 3:1-12 as part of the composition of Micah 1- 3 is material that comes from the period of the prophet's declamation with review of the cult. There is also the opinion that Micah 35- 8 gives a theological meaning to the false prophets. There's also the view that Micah 3:1- 12 points to the theology of the people's commination through the sumptuous exile. The theological exploration of this textbook is n't on one theological meaning alone because it's embedded in the period of the anthology's evolving environment. There are attempts by pens or editors to report complaints from colorful ages with the gradational development of textbooks over time that shape theology. The donation of the Deuteronomist editor makes the theological meaning of the textbook more comprehensive by integrating the social situation of the author. This composition shows the theological communication of the textbook of Micah 3: 1-12 through the social history approach of the textbook. The result of this exploration is to place the meaning of theology in the history of the life of the people by paying attention to the history of the publication of the textbook and the perceptivity of the editors in the period. AbstrakAdanya beragam penafsiran dari Mikha 3:1-12 menghasilkan pandangan teologi yang beragam pula. Khususnya ketika menafsir teologi kritik terhadap pemimpin agama dan pemerintah pada bagian teks. Terdapat pendapat bahwa Mikha 3:1-12 sebagai bagian dari komposisi Mikha 1-3 merupakan materi yang berasal dari periode orasi nabi dengan kritik terhadap kultus. Ada juga pendapat bahwa Mikha 3:5-8 memberikan pemaknaan teologi para nabi palsu. Ada pula pandangan bahwa Mikha 3:1-12 mengarah pada teologi penghukuman umat melalui pembuangan Babilonia. Penelitian teologi teks ini tidak pada satu makna teologi saja karena berakar pada periode konteks pembacanya yang berkembang. Terdapat usaha penulis atau redaktur yang melaporkan keluhan- keluhan dari periode yang beragam dengan perkembangan teks secara berangsur sepanjang waktu yang membentuk teologi. Kontribusi redaktur Deuteronomist menjadikan makna teologi teks menjadi lebih komprehensif dengan mengintegrasikan situasi sosial penulis. Tulisan ini memperlihatkan pesan teologi teks Mikha 3:1-12 melalui pendekatan sejarah sosial peredaksian teks. Hasil dari penelitian ini adalah menempatkan pemaknaan teologi dalam sejarah kehidupan umat dengan memerhatikan sejarah peredaksian teks dan kepekaan para redaktur pada periodenya.